245 OUTCOME OF EXTREMELY LOW BIRTH WEIGHT INFANTS TREATED WITH SURFACTANT (CUROSURF) AND NASAL CONTINUOUS POSITIVE ARIWAY PRESSURE: A RETROSPECTIVE ANALYSIS. Issue 1 (1st January 2007) - Gottipati, V.; McCoy, M.; Sekar, K.; Duke, J.
Abstract : Recent studies have shown a reduction in the need for mechanical ventilation in extremely low birth weight (ELBW) infants who are treated with surfactant followed by nasal continuous positive airway pressure (NCPAP). However, whether this therapy reduces the incidence of bronchopulmonary dysplasia (BPD) is uncertain. As we have been using this approach in ELBW infants we conducted a retrospective analysis using electronic data and hospital records of all infants at 500 to 1250 g who survived to 7 days of age from 1/5/2005 to 2/28/2006 ( n = 84), of whom 68 infants (BW −0.91 ± 0.19 kg, GA 26 ± 2 weeks) met the criteria for inclusion. Infants who did not receive surfactant were excluded from the study. Time of intubation, dosing of surfactant, and time of first extubation were recorded. If infants required reintubation, the timing of first reintubation was recorded, as well as the time of final extubation. Patients were grouped by those extubated to high-flow nasal cannula, NCPAP, and those that required reintubation. Indication for reintubation was recorded. Outcome data were collected looking at oxygen need at 36 weeks adjusted age (BPD), death, as well as secondary outcomes, including IVH greater than grade 2, ROP, NEC, and PDA requiring treatment. The results are shown in the Table . Conclusion: In our cohort of ELBW infants, 58% of infants did not require reintubation. In this group, the incidence of BPD was significantly reduced. Secondary outcomes (ROP, IVH, NEC) were statistically significant between the groups except for PDA and PDA treatment (Fisher's exact test).